Study of morbidity pattern among geriatric patients attending outpatient department of a rural health training center, Maner of IGIMS, Patna - Kumari, Seema; Bharati, Dharmvir Ranjan; Yadava, D. K.; ., Shahin; Sinha, Shivani; Kumari, Anju (International Journal Of Community Medicine And Public Health, 2019)
Background: With increasing life expectancy, number of old age people increased throughout the world, particularly more in the developing countries like India. Globally there are an estimated 605 million people aged 60 years and above. As the ageing population is increasing, the burden of their health problems is on a rise. To provide appropriate care for them there is a need to attain information about their morbidity pattern. Objectives: to study the morbidity pattern among the geriatric patients attending outpatient department of RHTC, Maner of IGIMS, Patna and to find out the difference in health problems between males and females, if any. Methods: This hospital based cross-sectional study was conducted during September 2017 to February 2018 among 98 elderly patients, aged 60 years or above, who attended first time at the Out Patient Department of rural health training center, Maner of IGIMS, Patna and who fulfilled inclusion criterion. Results: In this study majority had normal nutritional status. Amongst morbidity, prevalence of locomotors problems was highest (63.26%) followed by depression (42.85%), refractive error (20.4%), hearing loss (18.2%) and cataract (15.3). Locomotors problems were significantly higher in women (93.75%) as compared to the men (34%). However, the prevalence of depression, refractory error, hearing loss and cataract were not significantly associated with gender. Conclusions: There is a need to deliver comprehensive geriatric health care services for prevention and control of chronic diseases and address the dual burden of disease among the elderly to promote healthy ageing.